An Analysis of English Teachers’ IT (Information Technology) Ability for the Success of Online Learning - Hanny Fajar Pertiwi; Dila Charisma; Fitri Aprianti (National Conference on Language, Education, and Technology Proceeding, 2021)
Teacher's role is one of the important components in teaching and learning activities. In the learning process, teachers are required to be professional in order to educate and support the success of students’ learning. During the Covid-19 pandemic, both teachers and students are required to carry out online learning. Every teacher must carry out his duties in educating and teaching students without face-to-face meeting. This phenomenon will be a challenge for all teachers, including English teachers. During online learning, English teachers are required to develop information technology ability and be creative in making learning materials, in order to convey the material well and interestingly. Therefore, it is paramount to reveal the ability of Information Technology of the English teachers in order to make online learning successful and the obstacle in creating materials for online learning. This research uses the descriptive-qualitative method where data collection was done by giving questionnaires and also interviews so as to provide clear information. The object of this research were the English teachers at MAN 1 Kota Cirebon. The results obtained from the research shows that the English teachers at MAN 1 Kota Cirebon had a fairly good ability to make online learning successful, in terms of operating Information Technology devices, providing solutions for students who have difficulties, providing motivation, and also making materials for online learning. The obstacle that was faced by the teacher was in terms of a bad internet network so that it does not support the online learning process. Keywords: Teachers' Information Technology Ability; Information Technology; Online Learning.